2018
DOI: 10.1007/978-3-030-02683-7_13
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Communication Using Secrecy Capacity

Abstract: We address secure vehicle communication using secrecy capacity. In particular, we research the relationship between secrecy capacity and various types of parameters that determine secrecy capacity in the vehicular wireless network. For example, we examine the relationship between vehicle speed and secrecy capacity, the relationship between the response time and secrecy capacity of an autonomous vehicle, and the relationship between transmission power and secrecy capacity. In particular, the autonomous vehicle … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Vehicle-related parameters are very important for vehicle accidents and physical safety as parameters related to the operation of the vehicle while driving. The vehicle-related parameters include speed of the autonomous vehicle, the response time, etc., as mentioned by Ahn et al [11].…”
Section: Vehicle-related Parametersmentioning
confidence: 73%
See 1 more Smart Citation
“…Vehicle-related parameters are very important for vehicle accidents and physical safety as parameters related to the operation of the vehicle while driving. The vehicle-related parameters include speed of the autonomous vehicle, the response time, etc., as mentioned by Ahn et al [11].…”
Section: Vehicle-related Parametersmentioning
confidence: 73%
“…Ahn et al concluded that vehicle speed is closely related to the safety distance to prevent impulsiveness, and this safety distance ultimately affects secrecy capacity, resulting in a close relationship between vehicle speed and secrecy capacity, referring to Figure 2. The result was, surprisingly, that the faster the vehicle speed was, the less secrecy capacity was increased, rather than increasing (Figure 2) [11].…”
Section: Vehicle Speedmentioning
confidence: 97%
“…In this context, the secrecy performance over cascaded fading channels has been widely studied in [35][36][37][38][39][40]. Recently, the authors in [41] studied the secrecy capacity performance for vehicular communication networks. However, these works [35][36][37][38][39][40][41] were limited to the noncognitive networking setup.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the authors in [41] studied the secrecy capacity performance for vehicular communication networks. However, these works [35][36][37][38][39][40][41] were limited to the noncognitive networking setup. Moreover, the authors in [42,43] evaluated the performance of multihop cognitive radio networks over double-Rayleigh fading channels but without taking PHY-security aspects into account.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation